Venoarterial Extracorporeal Membrane Oxygenation for Postcardiotomy Shock-Analysis of the Extracorporeal Life Support Organization Registry - Kowalewski, Mariusz; Zieliński, Kamil; Brodie, Daniel; MacLaren, Graeme; Whitman, Glenn; Raffa, Giuseppe M; Boeken, Udo; Shekar, Kiran; Chen, Yih-Sharng; Bermudez, Christian; D'Alessandro, David; Hou, Xiaotong; et al. (Critical care medicine, 2021)
OBJECTIVES: Refractory postcardiotomy cardiogenic shock complicating cardiac surgery yields nearly 100% mortality when untreated. Use of venoarterial extracorporeal membrane oxygenation for postcardiotomy cardiogenic shock has increased worldwide recently. The aim of the current analysis was to outline the trends in use, changing patient profiles, and in-hospital outcomes including complications in patients undergoing venoarterial extracorporeal membrane oxygenation for postcardiotomy cardiogenic shock. DESIGN: Analysis of extracorporeal life support organization registry from January 2010 to December 2018. SETTING: Multicenter worldwide registry. PATIENTS: Seven-thousand one-hundred eighty-five patients supported with venoarterial extracorporeal membrane oxygenation for postcardiotomy cardiogenic shock. INTERVENTIONS: Venoarterial extracorporeal membrane oxygenation. MEASUREMENTS AND MAIN RESULTS: Hospital death, weaning from extracorporeal membrane oxygenation, hospital complications. Mortality predictors were assessed by multivariable logistic regression. Propensity score matching was performed for comparison of peripheral and central cannulation for extracorporeal membrane oxygenation. A significant trend toward more extracorporeal membrane oxygenation use in recent years (coefficient, 0.009; p < 0.001) was found. Mean age was 56.3 ± 14.9 years and significantly increased over time (coefficient, 0.513; p < 0.001). Most commonly, venoarterial extracorporeal membrane oxygenation was instituted after coronary artery bypass surgery (26.8%) and valvular surgery (25.6%), followed by heart transplantation (20.7%). Overall, successful extracorporeal membrane oxygenation weaning was possible in 4,520 cases (56.4%), and survival to hospital discharge was achieved in 41.7% of cases. In-hospital mortality rates remained constant over time (coefficient, -8.775; p = 0.682), whereas complication rates were significantly reduced (coefficient, -0.009; p = 0.003). Higher mortality was observed after coronary artery bypass surgery (65.4%), combined coronary artery bypass surgery with valve (68.4%), and aortic (69.6%) procedures than other indications. Lower mortality rates were observed in heart transplantation recipients (46.0%). Age (p < 0.001), central cannulation (p < 0.001), and occurrence of complications while on extracorporeal membrane oxygenation were independently associated with poorer prognosis. CONCLUSIONS: The analysis confirmed increased use of venoarterial extracorporeal membrane oxygenation for postcardiotomy cardiogenic shock. Mortality rates remained relatively constant over time despite a decrease in complications, in the setting of supporting older patients.
Keywords: kardiochirurgické výkony; Registries; Humans; Coronary Artery Bypass; transplantace srdce; lidé středního věku; mimotělní membránová oxygenace; registrace; Shock, Cardiogenic; Female; Aged; chirurgická náhrada chlopně; dospělí; mladý dospělý; Catheterization, Central Venous; věkové faktory; výsledek terapie; Catheterization, Peripheral; senioři; lidé; kardiogenní šok; Heart Transplantation; mortalita v nemocnicích; Extracorporeal Membrane Oxygenation; Cardiac Surgical Procedures; periferní katetrizace; Adult; ženské pohlaví; Male; Middle Aged; koronární bypass; Adolescent; prognóza; Treatment Outcome; katetrizace centrálních vén; Aged, 80 and over; Young Adult; senioři nad 80 let; Age Factors; Hospital Mortality; míra přežití; mužské pohlaví; Heart Valve Prosthesis Implantation; Prognosis; mladiství; Survival Rate